Reverse transcription-polymerase chain reaction (RT-PCR) assay for detection and characterization of Bean yellow mosaic virus (BYMV) in legumes applied by ICARDA’s GHU - Kumari, Safaa; Moukahel, Abdulrahman (International Center for Agricultural Research in the Dry Areas, 2023)
Bean yellow mosaic virus (BYMV) is distributed worldwide including CWANA and East Africa countries, and it is reported to occur on several legumes including faba bean, lentil, chickpea, field pea, grasspea, and a number of forage legumes, as well as a few non-legume hosts. A high incidence, up to 100%, has been noted in some regions of Egypt, Iraq and Sudan. BYMV is transmitted through seeds of most pulses, including faba beans, field peas, lentils, and lupins and through seed of several forage legumes and clovers. The virus is also transmitted by several species of aphids in a non-persistent manner. Early detection and accurate diagnosis of viral diseases is critical for the application of appropriate control measures. The last three decades have witnessed significant developments in improving the sensitivity of the methods to detect seed-borne viruses. The development of polymerase chain reaction (PCR) has greatly improved the sensitivity and utility of hybridization and other nucleic acid-based assays. Immunocapture-RT-PCR (IC-RT-PCR) is another alternative where virus particles are captured with the help of specific antibodies followed by their detection using PCR without isolating RNA. This hybrid diagnostic technique is more sensitive than ELISA and RT-PCR alone. In addition, Immunocapture of virus particles step provides a simple method to isolate virus particles from plant tissue, particularly when inhibitory substances are present, and thus enables subsequent use of RT-PCR amplification. Many primers for detecting BYMV viruses by RT-PCR have been reported. The current report describes a validated molecular tool (RT-PCR and IC-RT-PCR) for detection and characterization of BYMV in legumes applied by ICARDA’s GHU.